Effects of levosimendan in patients with severe functional mitral regurgitation undergoing MitraClip implantation. Issue 9 (September 2017) - Giannini, Cristina; Petronio, Anna S.; Fiorelli, Francesca; Liga, Riccardo; Spontoni, Paolo; De Carlo, Marco; Marraccini, Emilia; Pieroni, Andrea; Guarracino, Fabio
Abstract : Aim: Percutaneous mitral valve repair (PMVR) with a MitraClip device has been recently introduced as a valuable therapy in high surgical risk patients with functional mitral regurgitation (FMR) who are not responding to currently available medical treatments. Our aim was to assess the clinical, functional and prognostic impact of periprocedural levosimendan administration in patients with end-stage heart failure and FMR undergoing PMVR. Methods: Between December 2009 and August 2016, 94 consecutive high-risk patients with symptomatic FMR who underwent PMVR with the MitraClip System at our center were enrolled in a prospective registry. To identify two comparable groups of patients, 27 patients receiving levosimendan (No-L-group) were selected for the analysis matching by propensity score with those not treated with levosimendan (L-group). Results: Baseline demographics and echocardiographic variables were similar between the two groups. Acute procedural success was similarly high in both groups with no significant differences in procedural time and hospital outcomes. At discharge, echocardiographic parameters did not differ among groups except for higher value of right ventricle tissue Doppler imaging peak systolic-wave velocity in the L-group (10.7 versus 13.0 cm/s, P = 0.03, respectively). There was no significant difference in 1-year mortality between patients receiving levosimendan and those not treated with levosimendan. Conclusion: Prophylactic levosimendan did not affect long-term outcome in patients undergoing PMVR. However, levosimendan as an adjunctive therapy to MitraClip implantation offers further therapeutic advantages in patients with advanced heart failure by improving systolic right ventricle function.